2017
DOI: 10.1101/cshperspect.a022301
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TGF-β Signaling for Therapeutic Gain

Abstract: Transforming growth factor bs (TGF-bs) are closely related ligands that have pleiotropic activity on most cell types of the body. They act through common heterotetrameric TGF-b type II and type I transmembrane dual specificity kinase receptor complexes, and the outcome of signaling is context-dependent. In normal tissue, they serve a role in maintaining homeostasis. In many diseased states, particularly fibrosis and cancer, TGF-b ligands are overexpressed and the outcome of signaling is diverted toward disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 233 publications
2
139
0
Order By: Relevance
“…Conversely, inhibitory immunomodulatory cytokines such as TGF-β may be targeted in situ, specifically in the TME, to reduce their suppressive effects on NK cells. Once again, specific targeting of TGF-β in the TME is important due to potential toxicities associated with anti-TGF-β therapies administered systemically (290). Knudson et al reported an anti-PD-L1/TGFβ fusion protein (M7824), which depletes TGF-β signaling in the TME.…”
Section: Sensitizing Tumors For Nk Cell Killingmentioning
confidence: 99%
“…Conversely, inhibitory immunomodulatory cytokines such as TGF-β may be targeted in situ, specifically in the TME, to reduce their suppressive effects on NK cells. Once again, specific targeting of TGF-β in the TME is important due to potential toxicities associated with anti-TGF-β therapies administered systemically (290). Knudson et al reported an anti-PD-L1/TGFβ fusion protein (M7824), which depletes TGF-β signaling in the TME.…”
Section: Sensitizing Tumors For Nk Cell Killingmentioning
confidence: 99%
“…Elevated TGF-β expression correlates with tumor progression and poorer prognosis. Thus,various inhibitors for TGF-β signaling, e.g., ligand trap using the extracellular domain of TβRII, neutralizing antibodies against TGF-βs or TβRII, and inhibitors for TβRI and/or TβRII kinases, have been developed, and some of them are in clinical trials [103,195].…”
Section: Extracellular Regulation Of Tgf-β Signalingmentioning
confidence: 99%
“…Since only some patients respond to the immune checkpoint therapies, an important strategy to improve their efficacies may be combination with other immune therapies. Inhibition of TGF-β signaling is potentially a very interesting way to treat cancers, and many preclinical and clinical trials are ongoing [195]. Thus, combination of the immune checkpoint therapy with inhibition of TGF-β signaling may be an attractive strategy to treat cancers, especially those resistant to current immune checkpoint inhibitors.…”
Section: Application Of Garp For Cancer Immunotherapymentioning
confidence: 99%
“…On the other hand, researchers have investigated the efficacy of the TGFβ pathway inhibition in preclinical and clinical trials using several TGFβ antagonists, including TGFβ antibodies, antisense oligonucleotides, and receptorkinase inhibitors. In cancer, this inhibition could attenuate the TGFβ-dependent EMT; however, due to the pleiotropic functions of TGFβ signaling -which regulates many normal physiological functions and various steps of cancer progression -the effects of TGFβ inhibitors in cancer therapy remain unpredictable (63). Furthermore, the progressive cascade of events in cancer metastasis is activated by TGFβ, which recruits several cell types in the tumor microenvironment -not just primary tumor cells but also stromal and immune cells (64).…”
Section: Perspectivesmentioning
confidence: 99%